Design And Implementation of a Short Message Delivery System Using LoRa Technology - Sujono Sujono; Dwi Agung Sunaryo; Moh. Anshori Aris Widya (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
This study presents the design and development of a short message communication system capable of operating in areas without internet connectivity by leveraging LoRa (Long Range) technology. LoRa was selected due to its extended coverage and energy efficiency, making it well-suited for deployment in remote regions. The proposed system integrates ESP32-based transmitter and receiver nodes with the LoRa RA-01 module as the communication medium. A mobile application is developed to provide a user-friendly interface for composing and displaying messages, while an SQLite database is utilized for storing communication records locally. System development follows the Waterfall model, covering requirement analysis, design, implementation, and testing. Experimental results demonstrate that the system successfully transmits and receives messages up to a distance of 100 meters without internet connectivity. The solution offers a practical and efficient alternative for wireless communication, particularly for delivering critical information in areas underserved by conventional telecommunication infrastructure.